Balancing Roles: Effects on Female Employee Performance: Keseimbangan Peran: Dampak terhadap Kinerja Karyawan Perempuan - Dinar Dwi Choirunnisa; Dewi Andriani (Universitas Muhammadiyah Sidoarjo, 2022)
This research investigates the influence of dual role conflict, job stress, and emotional intelligence on the performance of married female employees in the finishing section of a manufacturing company. A quantitative approach was employed, utilizing a questionnaire to collect data from 87 participants selected through purposive sampling. The findings reveal that work-family conflict and work stress have a detrimental impact on the performance of female employees, while emotional intelligence positively affects their performance. These results emphasize the importance of addressing conflicts between work and family roles and managing job stress to enhance female employees' performance. Moreover, fostering emotional intelligence among female employees can contribute to improved performance outcomes. These findings provide valuable insights for organizations seeking to optimize the performance and success of their workforce. Highlights: Dual role conflict and job stress negatively affect female employee performance. Emotional intelligence positively impacts female employee performance. Quantitative research highlights the significance of addressing work-family conflict and managing job stress to enhance female employee performance. Keywords: Dual Role Conflict, Job Stress, Emotional Intelligence, Female Employee Performance, Quantitative Study.